IMPLEMENTASI METODE FIRST COME FIRST SERVED PADA PLATFORM RESERVASI LAPANGAN BADMINTON BERBASIS MOBILE - Uro Abdurohim; Dayanni Vera Versanika; Chandra Dirgantara (Jurnal Teknologi Informasi dan Komunikasi, 2022)
Many badminton court rental services still use a manual system, handling customer requests via telephone or online messaging apps such as WhatsApp. This approach makes it challenging to manage order data when there are many reservations. The First Come First Served (FCFS) algorithm is a method where the data entered first is processed first. The FCFS algorithm is commonly used in queuing systems because its orderly approach is well-suited for managing systematic queues. The design of this system utilizes the Extreme Programming method. This research aims to develop an online reservation system that simplifies the process for customers to rent courts and assists managers in promoting their facilities by implementing the FCFS method.